Pulmonary physiology is poorly associated with radiological extent of disease in systemic sclerosis-associated interstitial lung disease. Issue 5 (2nd May 2019) - Jhajj, Amrit; Gill, Harinder Pal; Hague, Cameron J.; Murphy, Darra; Elicker, Brett; Soon, Jeanette; Sulaiman, Nada; Castillo-Saldana, Daniela; Wilcox, Pearce G.; Dunne, James; Lee, Joyce S.; Wolters, Paul J.; et al.
Trials in systemic sclerosis-associated interstitial lung disease (SSc-ILD) typically use forced vital capacity (FVC) as the primary end-point [1, 2]; however, pulmonary function tests have limitations in SSc-ILD, notably being influenced by non-ILD factors such as pulmonary hypertension and diseases of the chest wall. High-resolution computed tomography (HRCT) may provide a more direct assessment of ILD severity, but HRCT-derived visual and quantitative scores also have limitations. The objective of this study was to determine the correlation of visual HRCT findings with severity, progression and mortality of SSc-ILD, and specifically whether HRCT findings and lung function measurements provide redundant or complementary measures of SSc-ILD severity and prognosis. Pulmonary physiology is poorly associated with radiological extent of disease in systemic sclerosis-associated interstitial lung disease http://ow.ly/Bx0X30o92aV